1991
DOI: 10.1111/j.1439-0418.1991.tb00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on indirect infection of Trypodendron lineatum Oliv. with Beauveria bassiana (Bals.) Vuill.

Abstract: The transfer of infection of B. bassiana from contaminated male T. lineatum to non‐contaminated females, as well as the effect of B. bassiana treated timber to the breeding activity and the mortality of young beetles in contaminated soil after immigration for hibernation was investigated. Breeding activity of non contaminated females is reduced by 20 % if placed together with contaminated males. Treated timber shows fewer holes of brood systems and less breeding activity than non‐treated one. The beetles were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
7

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
1
6
0
7
Order By: Relevance
“…In laboratory tests, Novák & Samsinakova (1962) found that B. bassiana caused 100% mortality of T. lineatum larvae in 6 to 8 days and 100% mortality of adults in 12 days. The latter authors also found that the effects of temperature, humidity, spore formulation, and spore dose on the infection of T. lineatum by B. bassiana were similar to those reported by Pražák (1988Pražák ( , 1991Pražák ( , 1997 for other bark beetle species, but different test conditions caused 36% to 55% mortality in most cases, while only a few experiments lead to mortality rates higher than 80% (Pražák 1988(Pražák , 1991(Pražák , 1997. Novák & Samsinakova (1962) reported that male beetles inoculated with B. bassiana transmitted the fungus to healthy female beetles and that the transmission reduced the number of eggs laid by 20%.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…In laboratory tests, Novák & Samsinakova (1962) found that B. bassiana caused 100% mortality of T. lineatum larvae in 6 to 8 days and 100% mortality of adults in 12 days. The latter authors also found that the effects of temperature, humidity, spore formulation, and spore dose on the infection of T. lineatum by B. bassiana were similar to those reported by Pražák (1988Pražák ( , 1991Pražák ( , 1997 for other bark beetle species, but different test conditions caused 36% to 55% mortality in most cases, while only a few experiments lead to mortality rates higher than 80% (Pražák 1988(Pražák , 1991(Pražák , 1997. Novák & Samsinakova (1962) reported that male beetles inoculated with B. bassiana transmitted the fungus to healthy female beetles and that the transmission reduced the number of eggs laid by 20%.…”
Section: Introductionsupporting
confidence: 68%
“…Novák & Samsinakova (1962) reported that male beetles inoculated with B. bassiana transmitted the fungus to healthy female beetles and that the transmission reduced the number of eggs laid by 20%. Application of B. bassiana spores to the bark surface reduced the number of egg niches by up to 44% depending on the spore concentration, and treatment of soil caused 88 to 100% mortality of hibernating offspring beetles (Pražák 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Soil application of pathogenic fungi has also been considered for the control of other insect pests that spend part of or all of entire life cycle in the ground. Treating soil with B. bassiana instead of treating timber induced a higher degree of infection in young hibernating striped ambrosia beetles, Trypodendron lineatum , which resulted in mortality rates of up to 100% (Prazak 1991). In addition, Metarhizium anisopilae (Hyphomycetes) applied on the soil at a low conidia rate provided respectively 82% and 97% of mortality in second and third instar June beetles, Phyllophaga anxia (Poprawski and Yule 1991).…”
Section: Discussionmentioning
confidence: 99%
“…They also stated that some treated females had 100% infected broods. Treated male adults transferred fungal inocula to untreated females which reduced their breeding activity by 20% (Prazak 1991). In summary, EPF did not only cause mortality of adult beetles outside in the host trees but also decreased beetles' population through infecting next-generation broods in the galleries.…”
Section: Resultsmentioning
confidence: 92%